2022
DOI: 10.3389/fpsyg.2022.815625
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Commognitive Responsibility Shift in Collaborative Problem-Solving During Computer-Supported One-to-One Math Tutoring

Abstract: The aim of this study is to use a commognitive responsibility framework to visualize responsibility shift in collaborative problem solving (CPS) during computer-supported one-to-one tutoring. Commognitive responsibility shift means that individuals’ cognitive responsibility shift can be reflected by the discourse in communication. For our sample, we chose a 15-year-old Chinese boy and his mathematics teacher with 6 years of teaching experience, both of whom have experienced computer-supported learning and teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Additionally, previous studies on blended learning have paid attention to secondary education, which have found that the commognition of the teacher and the student in a series of computer supported one-to-one online tutoring courses experienced three stages: teacher-led commognition process, comparison of commognitive process and student-led commognition process (Lu et al, 2019). Correspondingly, the commognitive responsibility gradually shifted from the teacher to the student (Lu et al, 2020), and the proportion of student-led collaborative problem solving increased (Lu et al, 2022). Such a blended course based on Constructivism makes students become increasingly agile in communication and cognitive interaction, and their cognitive level and class participation are gradually improved, which serves to cultivate critical thinking skills.…”
Section: Research Problemmentioning
confidence: 99%
“…Additionally, previous studies on blended learning have paid attention to secondary education, which have found that the commognition of the teacher and the student in a series of computer supported one-to-one online tutoring courses experienced three stages: teacher-led commognition process, comparison of commognitive process and student-led commognition process (Lu et al, 2019). Correspondingly, the commognitive responsibility gradually shifted from the teacher to the student (Lu et al, 2020), and the proportion of student-led collaborative problem solving increased (Lu et al, 2022). Such a blended course based on Constructivism makes students become increasingly agile in communication and cognitive interaction, and their cognitive level and class participation are gradually improved, which serves to cultivate critical thinking skills.…”
Section: Research Problemmentioning
confidence: 99%